2011
DOI: 10.1097/olq.0b013e3181f42093
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Toluidine Red Unheated Serum Test in the Diagnosis of HIV-Negative Neurosyphilis

Abstract: We retrospectively analyzed the Venereal Disease Research Laboratory test, Treponema pallidum particle agglutination test, and toluidine red unheated serum test (TRUST) in 41 cases of HIV-negative neurosyphilis and 34 non-neurologic syphilitic patient and found that serum-TRUST titers could be the indication of lumbar puncture in syphilitic patients and a reactive cerebrospinal fluid-TRUST is considered diagnostic to neurosyphilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…Our findings are consistent with the reports from Castro et al (5) regarding the performance of CSF-RPR and Jiang et al regarding the CSF-TRUST, which involved 24 and 41 neurosyphilis patients, respectively (6). In an earlier study in 1985, Larsen et al concluded that CSF-RPR and CSF-TRUST had statistically significantly lower sensitivities and specificities than CSF-VDRL; how- ever, their study was limited by a small sample of patients and older diagnostic techniques (14).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with the reports from Castro et al (5) regarding the performance of CSF-RPR and Jiang et al regarding the CSF-TRUST, which involved 24 and 41 neurosyphilis patients, respectively (6). In an earlier study in 1985, Larsen et al concluded that CSF-RPR and CSF-TRUST had statistically significantly lower sensitivities and specificities than CSF-VDRL; how- ever, their study was limited by a small sample of patients and older diagnostic techniques (14).…”
Section: Discussionsupporting
confidence: 93%
“…Compared to VDRL, the rapid plasma reagin test (RPR) and the toluidine red unheated serum test (TRUST) have similar test principles and performance using serum specimens, are easier to perform, and are available as commercial test kits (5,6). RPR and TRUST may be promising alternatives to VDRL when testing CSF for neurosyphilis; however, their use in routine clinical practice is currently controversial because of limited experience and published reports in the literature.…”
mentioning
confidence: 99%
“…The TRUST is a routine serological test for syphilis in China. It is reported that the specificity of the TRUST in neurosyphilis was 100%, which is the same as the VDRL [10]. Therefore, the diagnosis of neurosyphilis is also definite to our present patient because of the positive TPPA and TRUST in CSF.…”
Section: Discussionsupporting
confidence: 79%
“…7 Furthermore, in China, there are no commercial VDRL reagents that have been approved by the China Food and Drug Administration for CSF-VDRL examination, while multiple commercial toludine red unheated serum test (TRUST) reagents are available for use in the laboratory diagnosis of syphilis. 7,12 According to the reports in the published studies, 7,13,14 the CSF-TRUST may be used as an alternative for laboratory diagnosis of neurosyphilis in clinical settings when CSF-VDRL unavailable. So in the daily analysis of CSF samples, many clinical laboratories take TRUST as a substitute for the VDRL test.…”
Section: Introductionmentioning
confidence: 99%